2022
DOI: 10.24856/mem.v37i2.3013
|View full text |Cite
|
Sign up to set email alerts
|

The Examining of Entrepreneurial Intention Among Students with Entrepreneurial Education and Individual Value: Mediation Role of Human Capital

Abstract: <p>This study aims to examine the mediating role of human capital on the effect of entrepreneurial education and individual value on entrepreneurial intention. This research was conducted on students majoring in business at a university in Bali with a population of 7,246 people. A sample of 379 and data was collected using a questionnaire that returned as much as 279. Testing the research model using PLS-SEM with WarpPLS 7.0. The findings show that entrepreneurial education influence human capital, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…The impact of giving education about entrepreneurship offered by the universities on entrepreneurial intention is another area where study findings vary. According to the research's findings, entrepreneurial education and intention has been found correlated positively (Hoang et al, 2021;Kusumawijaya & Astuti, 2022;Martínez-Gregorio et al, 2021;Moses et al, 2016;Ndofirepi, 2020). Other studies' findings, there is a little correlation which happened between entrepreneurial intention and the entrepreneurial education provided (contrary with the research findings which were presented) (Amuda et al, 2019;Buana et al, 2017).…”
Section: Introductionmentioning
confidence: 82%
“…The impact of giving education about entrepreneurship offered by the universities on entrepreneurial intention is another area where study findings vary. According to the research's findings, entrepreneurial education and intention has been found correlated positively (Hoang et al, 2021;Kusumawijaya & Astuti, 2022;Martínez-Gregorio et al, 2021;Moses et al, 2016;Ndofirepi, 2020). Other studies' findings, there is a little correlation which happened between entrepreneurial intention and the entrepreneurial education provided (contrary with the research findings which were presented) (Amuda et al, 2019;Buana et al, 2017).…”
Section: Introductionmentioning
confidence: 82%